Evaluation of the Therapeutic Effects of the Hydroethanolic Extract of Portulaca oleracea on Surgical-Induced Peritoneal Adhesion - Ali Jaafari; Vafa Baradaran Rahimi; Nasser Vahdati-Mashhadian; Roghayeh Yahyazadeh; Alireza Ebrahimzadeh-Bideskan; Maede Hasanpour; Mehrdad Iranshahi; Sajjad Ehtiati; Hamed Rajabi; Mohammadreza Mahdinezhad; Hassan Rakhshandeh; Vahid Reza Askari (Mediators of Inflammation)
Objective. Peritoneal adhesion (PA) is an abnormal connective tissue that usually occurs between tissues adjacent to damaged organs during processes such as surgery. In this study, the anti-inflammatory and antioxidant effects of Portulaca oleracea (PO) were investigated against postoperative-induced peritoneal adhesion. Methods. Thirty healthy male Wistar rats (220±20 g, 6-8 weeks) were randomly divided into four groups: (1) normal, (2) control (induced peritoneal adhesion), and (3) and (4) PO extracts (induced peritoneal adhesion and received 100 or 300 mg/kg/day of PO extract for seven days). Finally, macroscopic and microscopic examinations were performed using different scoring systems and immunoassays in the peritoneal lavage fluid. Results. We found that the levels of adhesion scores and interleukin- (IL-) 1β, IL-6, IL-10, tumour necrosis factor- (TNF-) α, transforming growth factor- (TGF-) β1, vascular endothelial growth factor (VEGF), and malondialdehyde (MDA) were increased in the control group. However, PO extract (100 and 300 mg/kg) notably reduced inflammatory (IL-1β, IL-6, and TNF-α), fibrosis (TGF-β1), angiogenesis (VEGF), and oxidative (MDA) factors, while increased anti-inflammatory cytokine IL-10, antioxidant factor glutathione (GSH), compared to the control group. Conclusion. Oral administration of PO improved postoperational-induced PA by alleviating the oxidative factors, fibrosis, inflammatory cytokines, angiogenesis biomarkers, and stimulating antioxidative factors. Hence, PO can be considered a potential herbal medicine to manage postoperative PA. However, further clinical studies are required to approve the effectiveness of PO.